Recovery of Chronic Inflammatory Demyelinating Polyneuropathy on Treatment With Ocrelizumab in a Patient With Co-Existing Multiple Sclerosis. (9th March 2022) - Auer, Michael; Hegen, Harald; Hotter, Anna; Löscher, Wolfgang; Berek, Klaus; Zinganell, Anne; Fava, Elena; Rhomberg, Paul; Deisenhammer, Florian; Di Pauli, Franziska
The chimeric anti-CD20 antibody rituximab has demonstrated good efficacy as an off-label treatment in chronic inflammatory demyelinating polyneuropathy (CIDP), while the humanized anti-CD20 antibody ocrelizumab has been approved for treatment of multiple sclerosis (MS), whereas there is no evidence for its use in CIDP so far. We present a patient suffering from CIDP and MS, both refractory to standard treatment and both showing marked improvement on ocrelizumab. To the best of our knowledge, this is a unique report of CIDP with an almost full electrophysiological recovery on ocrelizumab which could be considered as a potential treatment option for refractory CIDP.